Objective necessity of introduction of organic farming in Ukraine Объективная необходимость внедрения органического земледелия в Украине - Sheludko Vitaliy N. (Bìznes Inform, 2013)
The article describes sharpening agro-ecological problems, negative consequences of intensification of farming, which influenced upon worsening the quality of land, pollution of soil and grown products with radionuclides, heavy metals and pesticides. It shows an objective necessity of introduction of organic farming in Ukraine, development of ecologically safe farming systems, which allow growing ecologically pure products of plant growing with progressing increase of soil fertility. Main components of organic farming are biologisation, soil-protective farming, application of soil-protective technologies of growing agricultural products. В статье раскрыто заострение агроэкологических проблем, негативные последствия интенсификации земледелия, которые повиляли на ухудшение качественного состояния земель, загрязнение почв и выращенной продукции радионуклидами, тяжелыми металлами, пестицидами. Показана объективная необходимость внедрения органического земледелия в Украине, разработки экологически безопасных систем земледелия, позволяющих выращивать экологически чистую продукцию растениеводства при прогрессирующем повышении почвенного плодородия. Основными составляющими органического земледелия является биологизация, почвозащитное земледелие, применение почвозащитных технологий выращивания сельскохозяйственных культур.